PRODUCTION OF FLY ASH FILTER FOR IRON REMOVAL IN GROUNDWATER - Madmanang, Romsan; Maprasit, Saudee; Thongmak, Narumol; Pradabphetrat, Piyaruk; Sathawong, Sidthipong; Boonkaew, Rachada (Srinakharinwirot University Journal of Sciences and Technology, 2023)
Fly ash is a potential material for iron removal because it contains oxides of silicate and aluminum, when in contact with water molecules develop anions and attract the cations of heavy metal ions to the adsorption site. Moreover, the modification of the filter with KMnO4 resulted in a higher surface area for iron removal. The aim of this research was to study the development of iron adsorbent and efficiency to reduce iron content in groundwater by using fly ash from biomass power plants. Two types of filter media were studied, namely, no burning and burning (500 ºC). All experiments, the fly ash was soaked at a concentration of 0%, 1%, 3%, 5%, 7% and 9% w/v of KMnO4 for 12 hours, then dried by heating the fly ash with a gas stove. Result of filter development was found that all concentrations of KMnO4, the iron content after the filtration tended to decrease with increasing filtration time, which the burning filter media had better water permeability than the no burning filter media. The study of iron removal efficiency in groundwater was revealed that all experiments of burning filter media were faster filtering time than no burning filter media when comparing at 50% of iron removal efficiency. The 0% KMnO4 concentration of burning filter media could reduce iron content in water from 0.69 mg/L to 0.25 mg/L within 1 hour, which passed the World Health Organization's Standard for drinking water quality while the no burning filter media took 3 hours. When considering the pH, it was shown that the pH increased with the increasing of filtering time and passed the highest approval criteria of the groundwater quality standard for consumption by the Department of Groundwater Resources.